2016
DOI: 10.1007/s13197-015-2159-7
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical, microbiological and spoilage analysis of probiotic processed cheese analogues with reduced emulsifying salts during refrigerated storage

Abstract: Microbial quality of low-salt processed cheeses supplemented with Bacillus coagulans spores (10 7 -10 8 CFU/g) relying on their physicochemical characteristics during 60 day-cold storage was evaluated. A reduction in moisture content, water activity and pH value and a significant enhancement in proteolytic index of control and probiotic samples were obtained by prolonging storage time. Survival rate of the probiotic cells significantly decreased up to day 30, while total count of the viable cells increased by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 48 publications
2
10
0
Order By: Relevance
“…Consequently, proteolysis significantly occurred in all treatments except the control and this could be due to the fermentation process of all treatments. These results agree with finding of Ehsannia and Sanjabi (2016) who showed that the PC manufactured using probiotic Bacillus coagulans had high WSN/TN and proteolytic activity toward casein by releasing its microbial intracellular peptidases.
Figure 2.Effect of fermentation using different starter cultures on the percentage of WSN/TN of spreadable PC during different cold storage periods.
…”
Section: Resultssupporting
confidence: 93%
“…Consequently, proteolysis significantly occurred in all treatments except the control and this could be due to the fermentation process of all treatments. These results agree with finding of Ehsannia and Sanjabi (2016) who showed that the PC manufactured using probiotic Bacillus coagulans had high WSN/TN and proteolytic activity toward casein by releasing its microbial intracellular peptidases.
Figure 2.Effect of fermentation using different starter cultures on the percentage of WSN/TN of spreadable PC during different cold storage periods.
…”
Section: Resultssupporting
confidence: 93%
“…Despite the analyses were carried out with the fresh cheese samples, results were similar to the ones displayed by Ehsannia and Sanjabi (2016), who added the probiotic microorganism B. coagulans in processes cheese samples and achieved a considerable reduction in the total count of molds and yeasts in 60 days of refrigerated storage.…”
Section: Microbiological Analysessupporting
confidence: 67%
“…Although the colors are interchangeable with low exposure to the acidic or basic agents [8] we have not tried it under this experiment. The pH indicators turn red eventually with time (Figure 7a) in the PE packaging due to the accumulation of lactic acid, pyruvate, acetate, or other organic acids by the metabolic activities of the microfauna [46]. The lowering of the pH in the PE package may be due to the symbiosis between the yeast and the bacteria [47], in contrast to the hydrogel environment where the pH remains almost the same due to the restriction in the post-processing microbial growth by curbing the water content in the packaging environment.…”
Section: Active and Intelligent Packagingmentioning
confidence: 99%